Integrability of Riccati equations and stationary Korteweg-de vries equations - Zhdanov, R. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
By using the Lie infinitesimal method, we establish the correspondence between the integrability of a one-parameter family of Riccati equations and the hierarchy of the higher Korteweg-de Vries equations.